A pro-competitive order as an institute of the economy based on knowledge; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Rozhdestvenskaya E. M. Elena Mikhailovna (2016, 2016)
Title screen